2020
DOI: 10.22541/au.159363375.57325180
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Equity in science education and disseminations: lessons learned during COVID-19 pandemics

Abstract: Scientific activities including university classes, wet lab research activities, fieldwork, and seminars/conferences have been cancelled in response to the ongoing COVID-19 pandemics. While the public health priority was to contain and mitigate the outbreak, the science sector swiftly adopted technologies to stay connected and continue the scientific activities as much as possible. Creativity, ingenuity, and resilience abound in the science community manifested in successful examples of truly global activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The "distance learning" or "home-based distance learning" requires a quiet and comfortable workspace equipped with technological devices and internet connection. However, the reality presented in Brazil and many other countries is an increasing economic disparity that doesn't allow every child to have a device and/or an internet connection (Petretto, Masala, & Masala, 2020;Yousefi, Abdollahzadeh, & Moossavi, 2020).…”
Section: Covid-19's Impacts On Education and Science Disseminationmentioning
confidence: 99%
See 1 more Smart Citation
“…The "distance learning" or "home-based distance learning" requires a quiet and comfortable workspace equipped with technological devices and internet connection. However, the reality presented in Brazil and many other countries is an increasing economic disparity that doesn't allow every child to have a device and/or an internet connection (Petretto, Masala, & Masala, 2020;Yousefi, Abdollahzadeh, & Moossavi, 2020).…”
Section: Covid-19's Impacts On Education and Science Disseminationmentioning
confidence: 99%
“…Besides, living in a busy or abusive house could also impact negatively the students' ability to engage in academic activities (Petretto, Masala, & Masala, 2020;Yousefi, Abdollahzadeh, & Moossavi, 2020). According to Armitage and Nellum (2020), research on the Ebola epidemic from 2014 to 2016 revealed that school closures during this period resulted in increased school dropouts, child labor, violence against children as well as higher pregnant adolescents.…”
Section: Covid-19's Impacts On Education and Science Disseminationmentioning
confidence: 99%